Multidisciplinary Treatment of Central Nervous System and Spinal Metastases on the Example of a Patient with Ovarian Cancer, Principles of Management. The Concept of Oligometastatic Disease. - Grzelak, Lech (Journal of Neurological & Neurosurgical Nursing / Pielęgniarstwo Neurologiczne i Neurochirurgiczne, 2025)
The development of modern diagnostic methods, surgical techniques, novel systemic treatment or radiotherapy makes it possible to achieve increasingly better results in the treatment of neoplastic disease. This is particularly noticeable in the approach to metastases of malignant neoplasms. Nowadays, the concept of oligometastatic disease, or otherwise metastatic disease, which we treat, significantly prolonging and improving the quality of life of patients, has appeared in the literature and in medical practice. Aim. The aim of the study is to show the multidisciplinary treatment of central nervous system and spinal metastases on the example of a patient with ovarian cancer. Case Report. The author of this paper would like to show, on the example of a fifty-year-old patient with ovarian cancer, how the application of modern treatment techniques has made it possible over the years to successfully treat multiple metastases to, among others, the brain and the spine. Discussion. I present the diagnostic and treatment regimen that has made it possible to control the Patient's cancer over the years. I demonstrate the interaction between different specialists and the decision-making process that guided us in taking certain actions. I show that this approach can be applied not only to a single case but also for general use. Conclusions. I would like to emphasise that only a multidisciplinary, hybrid approach to the problem of a neoplastic disease, especially in the area of metastases, promises further improvements in treatment outcomes.